Export and Competitiveness of Indonesian Coffee Bean in International Market: Strategic Implication for the Development of Organic Coffee Bean - Bambang Drajat; Adang Agustian; Ade Supriatna (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2007)
The performance of Indonesian coffee bean export from 1995 to 2004was not satisfactory. This implied that there were problems of the competitiveness of Indonesian coffee bean export. This study was expected to come up withsome views related with the problem. This study was aimed to analyze the competitiveness of Indonesian coffee bean export in international markets. Somepolicy implication would be derived following the conclusions. In addition,this study was aimed to deliver some arguments referring to organic coffee development as an alternative export development. Data used in this study wastime series data ranging from 1995 to 2004 supported with some primary data.The export data were analyzed descriptively and the Revealed ComparativeAdvantage (RCA) Index employed to analyze the competitiveness of Indonesian coffee bean export. The results of the analysis gave some conclusions, asfollows : (1) The export of Indonesian coffee bean was product oriented notmarket oriented. (2) The Indonesian coffee bean export was characterized withlow quality with no premium price, different from that of Vietnam coffee export. (3) Besides quality, the uncompetitive Indonesian coffee export was related to market hegemony by buyers, emerging issue of Ochratoxin A. contamination and high cost economy in export. (4) The competitiveness of Indonesian coffee export was lower than those other countries, such as Columbia,Honduras, Peru, Brazil, and Vietnam. (5) Indonesia still held opportunity todevelop organic coffee for export. Some policy implications emerged from thediscussion were as follows : (1) The Government should facilitate market development through the provisions of market information and export incentives.(2) The Government should develop and applied national standard of coffeebean referring to that of international, as well as, improve processing technology equipments in the farm level for both wet and dry process. (3) Besides improving quality, the improvement of competitiveness should also be carriedout by reducing up to elimination of operational costs before and in exportingports through the provisions of fiscal and monetary incentives (taxes and interest rates). (4) The development of coffee organic started with socializationof some aspects related to standard and implementation of farming, processing and trade. The Government should facilitate producers and exporters oforganic coffee with the provisions of market information and incentives.Key words: Export, coffee beans, competitiveness, organic coffee.